Searching for a Solution: A Case Report on Multifocal Ectopic Purkinje-Related Premature Contractions Syndrome - Monika Keževičiūtė; Neringa Bileišienė; Violeta Mikštienė; Germanas Marinskis; Jūratė Barysienė (Medicina)
Multifocal ectopic Purkinje-related premature contractions (MEPPC) syndrome is a recently recognized rare form of arrhythmia involving the entire His–Purkinje system and often coinciding with dilated cardiomyopathy (DCM). Certain variants in the SCN5A gene may be linked to MEPPC syndrome. We present a case of a 32-year-old Caucasian female who exhibited a high burden of premature ventricular contractions (PVCs) and non-sustained episodes of ventricular tachycardia (NSVT) with an alternating QRS pattern, and who was resistant to traditional medical therapy and radiofrequency catheter ablation (RFCA), necessitating implantation of a cardioverter-defibrillator (ICD). A positive family history (father’s death at the age of 40 years) and the rapid deterioration of left ventricular function parameters echocardiographically during recurrent arrhythmic episodes raised concern about a potentially complex disease scenario. Genetic testing revealed a heterozygous variant of the SCN5A gene, c.2440C>T, p.(Arg814Trp), confirming the diagnosis of MEPPC syndrome. Treatment with a combination of class I antiarrhythmic drugs, flecainide and mexiletine, concomitant with beta blockers, led to symptomatic improvement, a reduction of PVCs (from 66 491 (44%) to 858 (1%)), and the restoration of left ventricular function (LV EF from 44% to 53%). A lack of defined diagnostic criteria hampers timely diagnosis, leading to ineffective interventions and delayed initiation of treatment with antiarrhythmic drugs. MEPPC patients remain at significant risk for severe heart failure and sudden cardiac death. Our clinical case report underscores the importance of accurate and timely diagnosis, which allows effective treatment with a combination of antiarrhythmic drugs and mitigates the risk associated with MEPPC syndrome.